2015
DOI: 10.4238/2015.november.18.16
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and phylogeny of the 5' long terminal repeat from Brazilian bovine leukemia virus

Abstract: ABSTRACT. We conducted a phylogenetic analysis of 22 strains of bovine leukemia virus obtained by polymerase chain reaction to amplify a 582-base pair fragment of the transcriptional regulatory region 5' long terminal repeat (LTR). Twenty-two samples of proviral DNA from peripheral blood mononuclear cells containing bovine leukemia virus from naturally infected bovine from 4 distinct geographic regions in Brazil were investigated. The products obtained by polymerase chain reaction were subjected to direct sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Notably, these LTR sequences were more conserved than non-regulatory regions [ 22 ]. Recently, phylogenetic analysis of 5′ LTR sequences of BLV isolates from Brazil showed that these sequences clustered into five well-defined groups, with accumulation of nucleotide variability in the R-U5 region [ 23 ]. LTR variability has been correlated with altered BLV virulence and pathogeny [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, these LTR sequences were more conserved than non-regulatory regions [ 22 ]. Recently, phylogenetic analysis of 5′ LTR sequences of BLV isolates from Brazil showed that these sequences clustered into five well-defined groups, with accumulation of nucleotide variability in the R-U5 region [ 23 ]. LTR variability has been correlated with altered BLV virulence and pathogeny [ 24 ].…”
Section: Introductionmentioning
confidence: 99%